2011
DOI: 10.1103/physrevlett.107.190401
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Dipolar Bose-Einstein Condensate of Dysprosium

Abstract: We report the Bose-Einstein condensation (BEC) of the most magnetic element, dysprosium. The Dy BEC is the first for an open f -shell lanthanide (rare-earth) element and is produced via forced evaporation in a crossed optical dipole trap loaded by an unusual, blue-detuned and spinpolarized narrow-line magneto-optical trap. Nearly pure condensates of 1.5×10 4 164 Dy atoms form below T = 30 nK. We observe that stable BEC formation depends on the relative angle of a small polarizing magnetic field to the axis of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
900
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(924 citation statements)
references
References 59 publications
20
900
3
1
Order By: Relevance
“…In the presence of an axisymmetric nonlocal dipolar interaction [14] a 2D BEC soliton can be generated in a 1D harmonic [11] or a 1D optical-lattice [12] trap. Maucher et al [15] suggested that for Rydberg atoms, offresonant dressing to Rydberg nD states can provide a nonlocal long-range attraction which can form a 3D matter-wave droplet.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of an axisymmetric nonlocal dipolar interaction [14] a 2D BEC soliton can be generated in a 1D harmonic [11] or a 1D optical-lattice [12] trap. Maucher et al [15] suggested that for Rydberg atoms, offresonant dressing to Rydberg nD states can provide a nonlocal long-range attraction which can form a 3D matter-wave droplet.…”
Section: Introductionmentioning
confidence: 99%
“…As an impurity species we choose dysprosium -the most magnetic atom in the periodic table. Its bosonic and fermionic isotopes have been recently brought to quantum degeneracy 27,28 , which provides us a benchmark for comparison with other ultracold atomic experiments. We note that using matrix-isolated polar molecules 29 can potentially result in stronger dipole-dipole interactions between the impurities, however, decoherence due to coupling to phonons is also stronger for species possessing an electric dipole moment 30,31 .…”
Section: Magnetic Atom Impurities In Inert Matricesmentioning
confidence: 99%
“…However, intriguing phenomena are expected to occur in systems with dipolar interaction and this leads to rapidly growing interest in the preparation and study of dipolar quantum gases. Pioneering experiments have made use of magnetic dipolar interactions of atoms with large magnetic moments such as Cr [1] and more recently Er and Dy [2,3]. Even larger dipolar interactions can be realized making use of electric dipole-dipole interaction.…”
Section: Introductionmentioning
confidence: 99%